LEGAL POLITICS OF REGIONAL HEAD ELECTIONS DURING THE COVID-19 PANDEMIC: DO ANTAGONISTIC IMPLICATIONS? - Fifiana Wisnaeni; Kornelius Yosua Dimas Nugroho (Jurnal Pembaharuan Hukum, 2023)
This research aspires to know and analyze the political law of regional head elections in Indonesia in the midst of the COVID-19 pandemic. Next, the implications of COVID-19 are explored to determine its impact on the implementation of regional head elections and democracy in Indonesia. This study aims to analyze the political laws of regional head elections in Indonesia when the COVID-19 pandemic happened and explore the implications of the pandemic on regional head elections and democracy in Indonesia. This research used normative juridical method with specifications in the analytical descriptive investigation, secondary data was used to examine research data qualitatively. The study found that the rescheduled simultaneous regional elections during the COVID-19 pandemic were carried out in December 2020 while also applying stringent health protocols. The COVID-19 pandemic is believed not to have affected democracy in Indonesia since the process was carried out in a direct, open, public, secret, honest, and fair manner. this study also found that public participation in regional head elections amid the COVID-19 pandemic increased compared to previous years; voter turnout in 2015 was 69.35%, and the number increased to 74.89% in 2017. the participation further progressed to 76.09% in 2020 despite the happening pandemic.